PENYULUHAN PENYAKIT KANKER SERVIKS DI RT 16 KELURAHAN AIR HITAM KECAMATAN SAMARINDA ULU KOTA SAMARINDA - Apriyani, Apriyani; Izzah, Lailul (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
In Indonesia, cervical cancer ranks second in the order of malignancy in women, namely 16 people per 100,000 female population. Based on the Hospital Information System (SIRS) 2007, the incidence of cervical cancer was 5,786 cases or 11.78% of other malignancies. The incidence of cervical cancer increased from the number of cases in 2006 of 4,696 cases or 11.07% and about 70% of patients were in an advanced stage. Meanwhile, based on the Center for Data and Information of the Ministry of Health (2015), nationally, the prevalence of cancer in the age-old population in Indonesia is 1.4% or estimated to be around 347,792 people and for the East Kalimantan region itself there are 752 people. The purpose of this service is to provide counseling to women who are at risk of cervical cancer so that they can prevent it by implementing a clean and healthy lifestyle, for example not having sex with multiple partners and by increasing women's awareness to check their health, because when In Â this case, any disease can be treated and handled quickly, namely with early detection which is carried out regularly so as to reduce the risk of mortality. The high number of deaths caused by cervical cancer in Indonesian women occurs because the cancer is only known after entering an advanced stage. After attending and listening to socialization materials and conducting discussions, it was seen that public knowledge and understanding of cervical cancer increased. The participants from the service activities were very enthusiastic when they got the socialization materials presented by the speakers and then continued with discussions.